PENERAPAN METODE PEMBELAJARAN PROBLEM SOLVING UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Lina Herlina (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2019)
This research is motivated by the low student learning outcomes in respiration material at MAN 2 Bandung. Researchers solve these problems by applying problem solving learning methods. This study aims to improve student learning outcomes in respiration material at MAN 2 Bandung. The study was Classroom Action consisting of 2 cycles, each cycle consisting of 2 meetings. Each meeting consists of four stages: planning, action, observation and reflection. Classroom Action Research is an effort made by teachers in schools to improve the quality of learning or service, test the assumptions of educational theory in teaching practice and assess all educational activities in the education system. Setting The study was conducted in class XI MIPA 1 MAN 2 Bandung in semester Two of the 2018/2019 academic year. The number of XI MIPA 1 students consists of 8 men and 30 women. The results showed an increase in student learning outcomes from cycle I (57.9%) to cycle II (82.3%). Researchers concluded that problem solving can be used to improve student learning outcomes in Class XI MIPA 1 on respiration material at MAN 2 Bandung.